Suggested activities in high school biology on the effects of nutrient solutions on the growth and population of lemna minor - Jaurigue, Josefina L. 1948- (1977)
The study sought to develop and to try out laboratory activities on plant physiology and population that can be performed by high school biology students using Lemna Minor or duckweed as test specimen. To prepare the laboratory activities, a study of the effects of nutrient solutions on the growth and population of Lemna minor was first conducted. Results showed that Lemna minor grown in a complete nutrient solution, Hoagland's, has the same state when grown in its natural medium like creek or pond water. However, deficiency in one or more nutrients in the growth medium leads to an early or induced senescence, thus, resulting to an early death of the specimen.
Vita.
Thesis (M.A. Biology Education)--University of the Philippines, Diliman.
Keywords: Biology -- Study and teaching (Secondary) -- Activity programs -- Philippines -- Quezon City; Lemna minor -- Physiology; Plant physiology -- Experiments